Parâmetros nutricionais, ingestivos e bioquímicos de ovelhas alimentadas com rações contendo distintas quantidades de concentrado e silagem de milho inoculada - Magno, Leonardo Lopes (2017)
The aim of this work was to evaluate the nutritional, behavioral and biochemical parameters of ewes fed with corn silage inoculated with Lactobacillus buchneri, associated with different levels of concentrate (0%, 20%, 40%, 60% and 80%). Five female sheep were used, weighing 45.2 kg of the Santa Inês breed, were distributed in 5x5 Latin square in five periods, housed in metabolic cages. Blood samples were collected for biochemical and hematological evaluation of the animals during the experimental period, as well as measurement of the diet and water supplied and consumed, to measure consumption. The digestibility was performed by measuring the nutrients present in the fed diet and in the feces, calculating the difference between both. Dry matter (DM), crude protein (CP) and neutral detergent fiber (NDF) were analyzed. Also a study of intake behavior was promoted. In relation to the biochemical hepatic and protein components, cholesterol, triglycerides, very low density lipoprotein (VLDL), phosphatase, aspartate aminotransferase (AST), as well as albumin, uric acid, total protein creatine and urea, no significant differences were observed in the reference values. There was no effect of the use of inoculated silage associated with different amounts of concentrate on dry matter intake, dry matter intake in relation to body weight, dry matter consumption in relation to metabolic weight, water consumption and also on the relation between Water consumption and dry matter consumption, which may have been due to the fact that the animals were of the same category in relation to body weight, age and physiological state. The animals showed a high dietary intake and satisfactory digestibility. It was concluded that increasing levels of concentrate in the diet improved the responses on consumption and digestibility, without causing metabolic damage to the animals.